Considerations About How Emotional Intelligence can be Enhanced in Children With Autism Spectrum Disorder - Trevisan, Dominic A.; Abel, Emily A.; Brackett, Marc A.; McPartland, James C. (Frontiers in Education, 2021)
In this perspective paper, we review established areas of ASD emotional difficulties in relation to “emotional intelligence” (EI) theoretical frameworks. Existing literature suggests that people with ASD have lower EI on average in the domains of perceiving emotions from the environment and body language, using emotions to relate to other’s experience, understanding emotions based on contextual cues, and managing emotions in the self and others. Poorer EI in ASD may detract from academic success, even when cognitive intelligence is intact. We conclude by considering the manner in which EI interventions in special education classrooms and school settings, formerly termed “Social and Emotional Learning” (SEL) programs, can be adapted to promote EI in children with ASD.